Modulation in “Lifestyle” and “Travel” Rubrics from Garuda Indonesia Magazine - Ni Gusti Ayu Lintang Maha Dewi; I Wayan Ana; Kuntayuni Kuntayuni; Mas Trisnamayuni (Pusat riset dan Inovasi Nasional, 2026)
This research focusses on translators working with languages that have diverse promotional language systems and cultures. The study is based on the modulation theory given by Vinay and Darbelnet (1995). This research intends to highlight the changes in point of view produced by translators in translating texts from English into Indonesian. The data source of this study is Garuda Indonesia magazine, which is presented in English as well as its Indonesian translation. The research indicates that translators change their perspective based on various factors to produce a target language that is equivalent to the source language while retaining the original meaning. The changes include a) abstract for concrete, b) explicative modulation, c) the part for the whole, d) one part for another, e) reversal of terms, f) negation of opposite, g) active to passive, h) exchange of intervals for limits. The change in perspective creates a cultural bridge in translation involving different languages and cultures.